Freshwater transfer affected intestinal microbiota with correlation to cytokine gene expression in Asian sea bass - Morshed, Syed Monzur; Chen, Yu-Yi; Lin, Chia-Hao; Chen, Yen-Po; Lee, Tsung-Han (Frontiers in Microbiology, 2023)
As a catadromous fish, Asian sea bass (Lates calcarifer) juveniles migrate from seawater (SW) to freshwater (FW) for growth and development. During migration, they undergo physiological changes to acclimate to environmental salinity. Thus, it is crucial to understand how SW-to-FW migration affects the gut microbiota of catadromous fish. To the best of our knowledge, no study has revealed the effects of transfer to hypotonic environments on a catadromous fish microbiota. In this study, we aimed to determine the effects of FW transfer on the microbiota and cytokine gene expression in the intestines of juvenile catadromous Asian sea bass. The relationship between the water microbiota and the gut microbiota of this euryhaline species was also examined. We found that FW transfer affected both mucosa- and digesta-associated microbiota of Asian sea bass. Plesiomonas and Cetobacterium were dominant in both the mucosa- and digesta-associated microbiota of FW-acclimated sea bass. The pathogenic genera Vibrio, Staphylococcus, and Acinetobacter were dominant in the SW group. Although dominant fish microbes were present in the water, fish had their own unique microbes. Vitamin B6 metabolism was highly expressed in the FW fish microbiota, whereas arginine, proline, and lipid metabolism were highly expressed in the SW fish microbiota. Additionally, the correlation between cytokine gene expression and microbiota was found to be affected by FW transfer. Taken together, our results demonstrated that FW transfer altered the composition and functions of mucosa- and digesta-associated microbiota of catadromous Asian sea bass intestines, which correlated with cytokine gene expression.